Ecosystems and living resources of the Baltic Sea : their assessment and management - Ojaveer, E. (Springer, 2017)
This volume presents a reconstruction of the formation of the environmental conditions and biota in the present-day Baltic Sea area during the last glacial cycle and thereafter under the influence of extra-terrestrial, climatic and geological factors. Abiotic conditions in the contemporary Baltic Sea (water salinity, temperature, oxygen and light conditions, currents and other water movements) are characterized and in this background the natural regional system of the sea has been generated. Important issues are considered such as life forms in the Baltic and their dependence on the natural environment (both in the conditions of the relative stable environment and during the regime shifts), as well as anthropogenic influences and the basic differences between the areas of the World Ocean and the brackish Baltic Sea. This book also equips readers with basic principles of assessments and management of ecosystems and fish resources (including the long-term assessment and forecast on ecosystems and fish resources) and provides information on the structures of international collaboration developed in the Baltic Sea.
Keywords: Ecosystem management -- Baltic Sea.; Atlantic Ocean -- Baltic Sea.; elektronické knihy; electronic books